Determining Dynamic Characteristics Of Reinforced Concrete Minarets And Updating Of Their Finite Element Models Using Environmental Vibration Data - Yetkin, Musa; Calayır, Yusuf; Erkek, Hakan (Fırat University, 2018)
Structures are exposed to various dynamic effects such as earthquake, wind and traffic load. It need to be taken various measures for surviving the structures under dynamic loads. Taking the appropriate measures depends on the well-known of dynamic behavior of existing structures. This behavior of the structure can be known through analytical or experimental methods. In the analytical methods, many acceptance is made in finite element modeling of the structure and it is considered that the created model represents its existing case. However, it is rather difficult to fully represent of the existing structure with the accepted assumptions. In experimental methods, the dynamic characteristics of the structure (natural frequencies, mode shapes and damping ratios) are determined for the present case. Using these dynamic characteristics, the existing analytical model of the structure can be updated and the evaluation of the structure according to this new model can be made more realistic. In this study, analytical and experimental analyses of the minaret of Firat University Engineering Campus Mosque were carried out. The finite element model has been updated depending on the dynamic characteristics obtained from the experimental analysis.
Keywords: Engineering; Mühendislik